2012
DOI: 10.1055/s-0032-1325734
|View full text |Cite
|
Sign up to set email alerts
|

Added value of narrow band imaging and confocal laser endomicroscopy in detecting Barrett’s esophagus neoplasia

Abstract: HD-WLE in combination with NBI is highly accurate in the detection of HGD/IMC. Performing targeted biopsies in the surveillance of Barrett's esophagus is possible in expert centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…Without NBI, pCLE may have suboptimal sensitivity (12%) and PPV (18%) when used as a technique to potentially replace RB 28 . A recent non-randomized study reported a lower sensitivity of eCLE (75.7% without considering prior NBI) compared to HDWLE+NBI (89%) 29 . However, this 46 patient pilot study underpowered and the sensitivity of eCLE was low compared to other studies 13,30 .…”
Section: Discussionmentioning
confidence: 94%
“…Without NBI, pCLE may have suboptimal sensitivity (12%) and PPV (18%) when used as a technique to potentially replace RB 28 . A recent non-randomized study reported a lower sensitivity of eCLE (75.7% without considering prior NBI) compared to HDWLE+NBI (89%) 29 . However, this 46 patient pilot study underpowered and the sensitivity of eCLE was low compared to other studies 13,30 .…”
Section: Discussionmentioning
confidence: 94%
“…Although other emerging endoscopic imaging techniques have been proposed for this purpose or have even been shown to improve biopsy yield, 18,19 the advantage of VLE-guided biopsy is that the distal 6 cm of the esophagus is scanned in 3 dimensions at the microscopic level. The highest-yield biopsy sites can then be selected from this comprehensive microscopic dataset using cross-sectional microscopic morphologic criteria similar to those used for conventional histopathologic diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…New imaging technologies, such as narrow band imaging and confocal endomicroscopy, can enhance surface patterns associated with Barrett's esophagus. However, these imaging technologies ultimately require the use of endoscopy with or without topical or intravenous contrast agents [25, 26]. Targeted screening in high risk populations, such as those with chronic reflux who are over the age of 50, with a low cost screening device not requiring sedation would be ideal.…”
Section: Discussionmentioning
confidence: 99%